CANINE TECHNICAL SKILLS, SEARCH AND RESCUE IN DISASTERS: CONTRIBUTIONS OF NURSING TO PATIENT AND RESCUER SAFETY IN PRE-HOSPITAL OPERATIONS - Antonio Plautz Chocron, Marco; Da Silva Borges, Alexander (Journal of Interdisciplinary Debates, 2026)
Canine techniques in disaster search and rescue operations represent an essential multidisciplinary tool that integrates veterinary knowledge, specialized rescue techniques, and prehospital care. This systematic literature review of the past five years (2020-2025) examines the contributions of Nursing to the safety of both patients and responders in prehospital operations involving working dogs. Nine primary studies were identified in international databases (PubMed, Scopus, Web of Science, ScienceDirect, SpringerLink). Findings indicate that the integration of nursing professionals trained in urban search and rescue (USAR) operations significantly improves responder safety, reduces patient complications, and facilitates multidisciplinary coordination. Furthermore, infection control protocols, stress management, and occupational wellness are fundamental to the sustainability of rescue operations with dogs. It is concluded that Nursing plays a critical role in integrated safety, psychological well-being, and technical quality of prehospital disaster operations.